Emotional Aging: Taking the Immediate Context Seriously. Issue 3 (3rd July 2017) - Kunzmann, Ute; Isaacowitz, Derek
Abstract : The authors provide a review of selected laboratory research on age differences in emotional functioning. The authors propose that this research area would benefit from an ecological approach in which the immediate context of emotional functioning is more explicitly considered. More specifically, to date many laboratory studies have used stimuli and tasks with little ecological validity and did not explicitly consider the possibility that the research setting and stimulus material might have age-differential effects on the outcome measures. This practice may have led to inconsistent findings across studies and narrow or incorrect conclusions in terms of older adults' emotional functioning.